Principal leadership practices and teacher collegiality in Malaysian high performing schools / Corinne Jacqueline Perera - Perera, Corinne Jacqueline (2015)
The Malaysian Education Blueprint 2013 – 2025 stipulates that high performing school leaders are now more accountable for increasing or maintaining their school achievement outcomes. The intention of this study is to examine the leadership practices of principals’ in Malaysian high performing daily secondary schools in particular, the relationship between principal leadership practices and teacher collegiality. A mixed-methods research design was chosen for this study. Empirical data was gathered via a survey encompassing a sample of 290 school teachers followed by intensive data collection in 6 Malaysian high performing daily secondary schools. The data collection methods included semi-structured interviews, focus group discussions, questionnaires, documentary analysis and on-site observations at each of the school sites. This research study substantiates and affirms the central role that high performing school principals play in securing better performance. Conclusions from this study revealed a positive and moderate relationship between principal leadership practices and teacher collegiality. The findings from this study also highlighted that principals who are transformational and focus on building positive relationships with their teachers, make a significant and positive difference to teacher collegiality. This finding supports empirical work conducted in other countries and provides new evidence about the leadership practices of principals in high performing schools in Malaysia. This thesis reflects an interest in identifying successful principal leadership practices that can positively impact teacher collegiality and develop a learning environment conducive for student high achievements.